Cell Mechanics in Cancer: Integrating Mechanotransduction Pathways Within the Tumor Microenvironment - Sevgi, Merve; Isik, Yagmur; Karaca, Caner; Caglar, Esmahan; Abdioglu, Hasan Berkay; Zendel, Ferican; Basbinar, Yasemin; Uvet, Huseyin (WILEY, 2026)
Single-cell mechanical properties such as stiffness, elasticity, and viscosity, are crucial in governing biological processes like migration, proliferation, and differentiation. In cancer, the mechanical properties of cells undergo significant alterations, which contribute to tumor growth, metastasis, and resistance to therapy. This review focuses on cancer cell stiffness and explores how its regulation is disrupted by the complex interplay among cytoskeletal remodeling, nuclear mechanics, and extracellular matrix (ECM) interactions. Cancer-associated fibroblasts (CAFs) and ECM composition within the tumor microenvironment (TME) modulate cellular mechanics via mechanotransduction pathways involving Yes-associated protein/transcriptional coactivator with PDZ-binding motif (YAP/TAZ) and integrin-focal adhesion kinase (FAK) signaling. Increasing evidence supports cell stiffness as a promising diagnostic and prognostic biomarker, as well as a predictor of treatment response. Therefore, advanced techniques for measuring cell stiffness such as atomic force microscopy (AFM), Brillouin microscopy, and acousto-holography are evaluated with a focus on their potential clinical applicability. However, translation into routine oncology practice remains limited by technical variability, lack of standardized protocols, and the need for large-scale clinical validation. This review highlights the potential of integrating biomechanical markers into clinical workflows as a means to advance cancer diagnostics and enable more personalized therapeutic strategies.
Keywords: BETA-CATENIN ACTIVATION; EXTRACELLULAR-MATRIX; ACTIN-FILAMENTS; BREAST-CANCER; SOLID STRESS; STIFFNESS; COLLAGEN; TISSUE; CYTOSKELETON; FIBROBLASTS; Cell Biology; Physiology